2016
DOI: 10.1097/jom.0000000000000715
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Long Working Hours, Physical Inactivity, and Burnout

Abstract: Long working hours are correlated with burnout when working over 40 hours per week and is even stronger when working over 60 hours per week. Limiting working hours to 40 weekly may be beneficial for the prevention of burnout. Physical activity helps reduce the risk of burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
72
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 31 publications
(29 reference statements)
15
72
1
4
Order By: Relevance
“…This results are consistent with the literature that points to the high psychosocial risk at work of bus drivers in comparison with other occupational groups [3,4], and with the evidence on the association between work stress, burnout, and negative organizational outcomes [10,37]. In particular, the aforementioned findings support the evidence that job strain and burnout are risk factors for road incidents in the public bus transport systems [5,8,47], occupation in which long working hours (as observed in the results) explain a risk increasing in terms of objective risk factors at work, such as in other high vulnerable groups [74][75][76].…”
Section: Discussionsupporting
confidence: 76%
“…This results are consistent with the literature that points to the high psychosocial risk at work of bus drivers in comparison with other occupational groups [3,4], and with the evidence on the association between work stress, burnout, and negative organizational outcomes [10,37]. In particular, the aforementioned findings support the evidence that job strain and burnout are risk factors for road incidents in the public bus transport systems [5,8,47], occupation in which long working hours (as observed in the results) explain a risk increasing in terms of objective risk factors at work, such as in other high vulnerable groups [74][75][76].…”
Section: Discussionsupporting
confidence: 76%
“…One study reported that stress levels of female managers were as high after work as during work, whereas among male managers, stress levels rapidly decreased when the working day ended [7]. Even when physical inactivity was controlled for in the analysis, gender differences existed in the presentation of burnout [8]. Exhaustion was consistently found to be more prevalent among women than men [9].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the criteria of “fatigue is not substantially alleviate by rest,” if a person indicated that the person’s problem with fatigue/energy entirely went away with rest, they would be excluded. For the item involving “fatigue is the result of excessive exertion,” Hu et al [31] found that long working hours are correlated with burnout when working over 40 hours per week and is even stronger when working over 60 hours per week. Therefore, individuals who indicated that combined work related activities or household activities involved 60 or more hours a week, for the past 4 weeks, would be considered exclusionary.…”
Section: Methodsmentioning
confidence: 99%